Zero-sequence voltage compensation of a distribution network through a four-wire modular multilevel static synchronous compensator. (July 2019) - Duarte, Samuel N.; Ghetti, Frederico T.; de Almeida, Pedro M.; Barbosa, Pedro G.
Highlights: Zero-sequence network voltage compensation strategy. Modular mulitlevel static synchronous compensator. Control algorithm for four-wire static synchronous compensator. Abstract: This paper presents a zero-sequence voltage compensation strategy for a three-phase four-wire modular multilevel static synchronous compensator used to regulate the network voltages. The control strategy is based on a synchronous reference frame mathematical modelling used to control the positive and zero-sequence voltages and currents of a MMC static synchronous compensator. The static compensator is controlled to synthesize AC currents in such a way to restore the positive-sequence voltage to its rated value and to mitigate the zero-sequence voltage at the point of common coupling. Digital simulations are presented to validate the static synchronous compensator mathematical analysis and to demonstrate the performance of the proposed control strategy.